The Relationship between the Character and Place in the Novel " Ba’d Raheel Alsamt" - Alaa Kadhim Rupa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
children living in the same neighborhood and in the same school, sharing toys and family ties. As they are getting older , their intellectual and mental beliefs grow up. They suffer from injustice , abusiveness and marginalization of their rulers. They meet a teacher and they have an intimate relationship. He implants in them the love of the homeland and resistance to injustice. They join one of the resistance movements against the Ba’athist rule at that time The novel records different events in different places and different characters. The place is a group of alleys and neighborhoods of Amarah (i.e., a town in the southern Iraq) where the events of the novel take place. The movement of characters in different places leads to the transformation of some open spaces into a battlefield and become as if they are closed and lonely due to the change in the conditions of the characters from absurdity to commitment and their rebellion against the unjust authority and the revolution against it